Analysis of FTIR Spectra, Flavonoid Content and Anti-Tyrosinase Activity of Extracts and Lotion from Garcinia schomburgkiana by Multivariate Method - Thummajitsakul, Sirikul; Silprasit, Kun (Trends in Sciences, 2022)
In this study, fourier transform infrared (FTIR) study, total flavonoid content and anti-tyrosinase activity of leaf, seed and flesh extracts of Garcinia schomburgkiana and lotion formulation from the extracts were carried out. Additionally, a relationship among FTIR spectra, total flavonoid content and anti-tyrosinase activity was analysed by partial least squares structural equation modelling (PLS-SEM) and principal component analysis (PCA) analysis. The result indicated that the highest total flavonoid content was found in leaf ethanol extract (214.00 ± 7.32 mg rutin equivalent per mg extract). For lotion samples, lotion containing leaf ethanol extract revealed the strongest level of total flavonoid content (5.51 ± 0.04 mg rutin equivalent per mL lotion). Moreover, anti-tyrosinase activity was observed in lotion containing the extracts (1/EC50 ranged from 0.0063 to 7.2334) higher than that of aqueous, ethanol and propanediol extracts (1/EC50 ranged from 0.0099 to 0.5319). The FTIR result confirmed the presence of various function groups in different parts of G. schomburgkiana and lotion samples, which involved the structure of flavonoids namely O-H stretch, C=O bending vibrations, unsaturation bonds, phenol or tertiary alcohol (O-H bend), C-O-H deformation and C-O stretching vibrations of aromatic ethers. The PLS-SEM analysis indicated a moderate positive relationship between the total flavonoid content and FTIR data, significantly (β = 0.502, t = 2.239, p-value < 0.05). The FTIR and subsequent PCA analysis could differentiate of aqueous, ethanol and propanediol extracts and lotion samples. HIGHLIGHTS FTIR data positively correlated with total flavonoid content Extract and lotion samples revealed total flavonoid content and anti-tyrosinase activity The PLS-SEM analysis showed significantly positive relationship between the total flavonoid content and FTIR data FTIR and subsequent PCA analysis differentiated extracts and lotions GRAPHICAL ABSTRACT